Competitive exclusion after invasion? - Bøhn, Thomas; Amundsen, Per-Arne; Sparrow, Ashley (Biological Invasions, 2007)
This is a post-peer-review, pre-copyedit version of an article published in Biological Invasions . The final authenticated version is available online at https://doi.org/10.1007/s10530-007-9135-8 . The ‘Competitive Exclusion Principle’ is a foundation stone in the understanding of interspecific competition and niche relationships between species. In spite of having the status of a biological law, the principle has limited empirical support. In this study, we document strong effects of competition from the invading fish species vendace Coregonus albula over a 14-year period in the sub-arctic Pasvik watercourse. The native d.r. whitefish, that shared food and habitat niche with the invader, was displaced from its original niche and showed a more than 90% decline in population density over the study period. The study thus provides a unique record of how an exotic fish species excludes a native species from its original niche. Our data support the competitive exclusion principle, but also indicate that the vulnerability of the inferior competitor depends on a lack of alternative resources and on indirect ecological interactions.